Predictors of Cognitive Decline in 85-Year-Old Patients Without Cognitive Impairment at Baseline: 2-Year Follow-Up of the Octabaix Study. (March 2013) - Formiga, Francesc; Ferrer, Assumpta; Chivite, David; Alburquerque, Jesus; Olmedo, Claudia; Mora, Jose Maria; Labori, María; Pujol, Ramón
Background/Rationale: To determine how many 85-year-old community-dwelling patients with good cognitive performance at baseline maintain this level at 2-year follow-up. Methods: We realized a longitudinal community-based study including 169 inhabitants. Patients who maintained scores >23 on the Spanish version of the Mini-Mental State Examination (MEC) were compared with the rest. Results: A total of 144 individuals (85.2%) were found maintaining a MEC score >23. Under the combined criteria 110 (65%) presented no new cognitive decline. Multiple logistic regression analysis showed that maintaining a MEC score >23 was significantly associated with having a higher MEC score at baseline ( P < .001, odds ratio 1.280, 95% confidence interval 1.104-1.484). Conclusion: Most oldest-old patients with good cognitive function at baseline maintain this level at 2-year follow-up.